2015
DOI: 10.1186/s13256-015-0756-8
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in infantile myofibromatosis and fibromuscular dysplasia: a case report

Abstract: IntroductionWe report what we believe to be the first case of a child affected by two rare vascular diseases complicated by kidney failure and successfully treated by kidney transplantation.Case presentationA 3-year-old Caucasian girl with fibromuscular dysplasia and infantile myofibromatosis presented with arterial hypertension and renal failure. She received a deceased donor kidney transplantation distal to an iliac graft. The technical peculiarities of this transplantation are described, as well as her favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Rapid progression of mild FMD one year after transplantation have been reported, suggesting FMD cannot be considered benign in a potential normotensive renal donor [ 9 ]. Nevertheless, it has also been reported that carefully selected patients with FMD have been successfully used as renal donors [ 18 20 , 24 , 25 ]. In fact, among asymptomatic renal donors with FMD presenting mild irregularity and no significant stenosis of the renal artery, none of them exhibited hypertension, proteinuria, or significant changes in serum creatinine level throughout a mean follow up of 4,5 years after donation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid progression of mild FMD one year after transplantation have been reported, suggesting FMD cannot be considered benign in a potential normotensive renal donor [ 9 ]. Nevertheless, it has also been reported that carefully selected patients with FMD have been successfully used as renal donors [ 18 20 , 24 , 25 ]. In fact, among asymptomatic renal donors with FMD presenting mild irregularity and no significant stenosis of the renal artery, none of them exhibited hypertension, proteinuria, or significant changes in serum creatinine level throughout a mean follow up of 4,5 years after donation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second was a man with segmental overgrowth, thin, discolored skin, and multiple intra‐ and extracranial fusiform aneurysms with a different GOF variant (Karasozen et al, 2019). Notably, fusiform cerebral, coronary, and renal aneurysms have all been reported in individuals with constitutional PDGFRB GOF phenotypes (Brasseur et al, 2010; Frezin, Fusaro, Reding, & Godefroid, 2015; Zarate et al, 2019; Zufferey et al, 2013). More restricted mosaic GOF variants of PDGFRB found only in affected tissue have been seen in sporadic myofibromas, and less often in myopericytomas and fusiform aneurysms (Arts et al, 2016; Hung & Fletcher, 2017; Karasozen et al, 2019; Zhong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The second was a man with segmental overgrowth, thin, discolored skin, and multiple intra-and extracranial fusiform aneurysms with a different GOF variant (Karasozen et al, 2019). Notably, fusiform cerebral, coronary, and renal aneurysms have all been reported in individuals with constitutional PDGFRB GOF phenotypes (Brasseur et al, 2010;Frezin, Fusaro, Reding, & Godefroid, 2015;Zarate et al, 2019;Zufferey et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates up to 76-93%, often due to cardiopulmonary or gastrointestinal complications, were observed in published cohorts of 28 to 31 children with multicentric disease with multiple visceral IM lesions [33,36,40]. Of note, aneurysms and fibromuscular dysplasia were reported in patients after a prior diagnosis of sporadic IM [15, [41][42][43]. A few children with sporadic IM were also reported to develop malignant tumors in addition to IM: fibrosarcomatous transformation of a congenital solitary IM was observed in a 14-months-old child [44].…”
Section: Outcomementioning
confidence: 99%